Profiling of plasma extracellular vesicles identifies proteins that strongly associate with patient’s global assessment of disease activity in rheumatoid arthritis - Arntz, Onno J.; Thurlings, Rogier M.; Blaney Davidson, Esmeralda N.; Jansen, Pascal W. T. C.; Vermeulen, Michiel; Koenders, Marije I.; van der Kraan, Peter M.; van de Loo, Fons A. J. (Frontiers in Medicine, 2024)
Background: Rheumatoid arthritis (RA) is an autoimmune disease characterized by chronic synovial inflammation and cartilage/bone damage. . Intercellular messengers Cytokines like IL-1 and TNF, play a crucial role in the pathophysiology of RA but have limited diagnostic and prognostic value. Therefore we assessed whether the protein content of the Rrecently discovered, extracellular vesicles (EVs), which have gained attention in the pathogenesis of this diseaseRA, correlate with disease activity parameters but which processes they reflect in RA patients. is unknown.We identified and quantified proteins in plasma-derived EVs (pEVs), isolated by size exclusion chromatography from 17 RA patients by mass spectrophotometry (MS). Quantified protein levels were correlated to with laboratory and clinical parameters, and the patient's own global assessment of their disease activity (PGA-VAS). In a second MS run, pEV proteins of 9 other RA patients were quantified and compared to those from 9 healthy controls (HC).Results: No differences were observed in concentration, size, and protein content of pEVs from RA patients. Proteomics revealed >95% overlapping proteins in RA-pEVs, compared to HC-pEVs (Data are available via ProteomeXchange with identifier PXD046058). Remarkably, in both runs, the level of far more RA-pEV proteins correlated positively to PGA-VAS than to either clinical or laboratory parameters. Interestingly, all observed PGA-VAS positively correlated RA-pEV proteins were associated to with the actin cytoskeleton linker proteins Ezrin and Moesin.Our observation suggest that PGA-VAS (loss of vitality) may have a different underlying pathological mechanism in RA, possibly related to enhanced muscle actincytoskeleton activity. Furthermore, our study contributes to the growing awareness and/ evidence that pEVs contain valuable biomarkers for diseases, with added value in/for RA (patients).